Risk Factors for Sexual Dysfunction among Postpartum Women in Kuantan, Pahang - Abd Aziz, Karimah Hanim; Jamani, Nurjasmine Aida; DrKhalid, Nur Nadrah; Draman, Nani (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Sexual dysfunction after childbirth is reported to be prevalent worldwide. The risk factors for sexual dysfunction is still underexplored. Thus, this study aims to determine the possible risk factors associated with sexual dysfunction among post-partum women. MATERIALS AND METHODS: This cross-sectional study was conducted in nine primary care clinics in Kuantan involving 420 women within six months postpartum. The respondents were conveniently sampled and completed the data collection forms comprising of their socio[1]demographic data, the Malay version Female Sexual Function Index (MVFSFI) Questionnaire to measure the sexual dysfunction score. Descriptive analysis, Chi-square test, and binary logistic regression were used for data analysis. RESULTS: Among the women sampled, those with higher education had a 72% increased risk of developing postpartum sexual dysfunction (aOR=1.72, 95%CI=1.01,2.81). Women who practised non-hormonal contraception were a 42% lower risk of getting postpartum sexual dysfunction as compared to those who consumed hormonal contraception (OR=0.58, 95%CI=0.35,0.95). CONCLUSION: Education level is associated with a higher risk of developing postpartum sexual dysfunction. Non-hormonal contraceptive methods were found as a protective factor for developing postpartum sexual dysfunction. Therefore, doctors can advise those postpartum women with sexual dysfunction and on hormonal contraception to change to non-hormonal methods.